The Effectiveness of Case-Based STEM Integrated with Mobile Simulation to Foster Students’ Creative Thinking Skills - Nurita, Tutut; Yuliati, Lia; Mahdiannur, Muhamad Arif; Ilhami, Fasih Bintang (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aims to determine the effect of case-based science, technology, engineering, and mathematics (STEM) integrated with mobile simulation on fostering students’ creative thinking skills. This study utilized an experimental design, specifically a pretest-posttest control group design. The research subjects were 40 students from a university in Surabaya City. The research instrument used was a test measuring creative thinking ability. The data was analyzed using the Wilcoxon non-parametric test because it was not normally distributed. The results showed that: (1) there is a statistically significant difference between the initial test and the final test; (2) there is a significant increase in the creative thinking ability of students who participate in oscillation-based STEM Embedded learning with mobile simulation; (3) there is a positive relationship between the use of mobile simulation and students’ STEM Embedded creative thinking ability. The conclusion of this study is that case-based STEM embedded oscillation with mobile simulation is effective in improving students’ creative thinking skills.